Maximum locomotor speed of the best football players at the FIFA World Cup in brazil - Bojkowski, L.; Sliwowski, R.; Wieczorek, A. (Central European Journal of Sport Sciences and Medicine, 2016)
In comprehensive preparation of a player to football competition special attention is paid to his predispositions in terms of speed abilities. Therefore, the authors` objective was to analyse maximum locomotor speed of players of the four best national teams competing during the FIFA World Cup in Brazil, including specifying the differences in terms of speeds of these national teams and players in corresponding playing positions of individual teams. The analysis used data obtained using the Castrol Performance Index, a kinematic method and in order to present significance of differences between the studied teams and playing positions one-way analysis of variance (ANOVA) was performed. The study showed that the mean maximum running speed of the players of the four best teams of the World Cup was 8.34 metres/second. The mean maximum locomotive speed of the defenders in semi-finalist teams of the tournament was 8.29 m/s, while the midfielders` speed was - 8.16 m/s, the forwards` - 8.48 m/s and the goalkeepers` - 7.40 m/s. The players who had a maximum speed of 9 m/s or more were the Dutchman Ron Vlaar (9.16 m/s) and the Argentines José María Basanta (9.09 m/s) and Ángel Di Maria (9.17 m/s). There is no significant difference between the world`s best teams, including between their corresponding playing positions, in the level of maximum running speeds determining the dynamics of the game.